2009
DOI: 10.1038/emboj.2008.284
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of the 2 Cl−/1 H+ antiporter ClC-5 in a NO3−/H+ antiporter by a single point mutation

Abstract: Several members of the CLC family are secondary active anion/proton exchangers, and not passive chloride channels. Among the exchangers, the endosomal ClC‐5 protein that is mutated in Dent's disease shows an extreme outward rectification that precludes a precise determination of its transport stoichiometry from measurements of the reversal potential. We developed a novel imaging method to determine the absolute proton flux in Xenopus oocytes from the extracellular proton gradient. We determined a transport sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
124
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(142 citation statements)
references
References 37 publications
18
124
0
Order By: Relevance
“…They increased ϳ3-fold in the presence of extracellular NO 3 Ϫ (Fig. 5E), coinciding with the recent parallel work by Zifarelli and Pusch (38). Whereas currents of WT ClC-5 are also larger with NO 3 Ϫ than with Cl Ϫ (Fig.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…They increased ϳ3-fold in the presence of extracellular NO 3 Ϫ (Fig. 5E), coinciding with the recent parallel work by Zifarelli and Pusch (38). Whereas currents of WT ClC-5 are also larger with NO 3 Ϫ than with Cl Ϫ (Fig.…”
Section: Resultssupporting
confidence: 76%
“…ϩ exchange both in the present study as well as in parallel work by Zifarelli and Pusch (38). A novel method (43) to measure proton transport allowed these authors to show that ClC-5(S168P) had gained an NO 3 Ϫ /H ϩ coupling ratio of ϳ2 at voltages between ϩ40 and ϩ60 mV, indistinguishable from that for Cl Ϫ /H ϩ exchange (38).…”
Section: /Hsupporting
confidence: 49%
See 1 more Smart Citation
“…It is expressed in different cell types in vesicles of the endocytotic-lysosomal pathway; in osteoclasts, ClC-7 is localized also in the ruffled border and is involved in the acidification of the resorption lacuna. Recently it has been shown that, as previously suggested by work on bacterial ClC homologues, the ClC-7 protein and other members of the ClC family are not passive chloride ion channels, but rather secondary active chloride/proton antiporters (Accardi & Miller, 2004;Picollo & Pusch, 2005;Scheel et al, 2005;Graves et al, 2008;Zifarelli & Pusch, 2009).…”
Section: Introductionmentioning
confidence: 82%
“…Residue S107 in this sequence appears to be an intracellular gate to the Cl − -permeation pathway (3,10). Mutations at 107 unvaryingly disrupt anion transport, with mixed effects on H + transport (21,25,(42)(43)(44). The surgical precision with which I109F retards H + transport demonstrates that different regions of the GSGIPE signature sequence can have separable effects on H + and Cl − transport, despite the close juxtaposition of the H + /Cl − pathways at this region of the protein.…”
Section: Discussionmentioning
confidence: 99%